2019
DOI: 10.1111/pedi.12838
|View full text |Cite
|
Sign up to set email alerts
|

Associations of growth from birth to puberty with glycemic indicators at ~17.5 years: Evidence from Hong Kong's “Children of 1997” birth cohort

Abstract: Background From an evolutionary biology perspective, where growth and reproduction trade‐off against longevity, we assessed the associations of growth from birth to puberty by phase with later glycemic indicators and any differences by sex. Methods In the population‐representative Hong Kong Chinese “Children of 1997” birth cohort (n = 8327), the relation of initial size (weight‐for‐age z score (WAZ) at birth, length/height‐for‐age z score (LAZ) at 3 months or body‐mass‐index‐for‐age z score (BAZ) at 3 months b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
(119 reference statements)
0
1
0
Order By: Relevance
“…Substantial evidence has demonstrated that an earlier timing of puberty is associated with poorer mental and physical health in later life [3][4][5][6][7]. While the underlying mechanisms remain unclear, greater childhood growth and obesity have been associated with both earlier puberty [8] and adverse health outcomes [9][10][11][12][13]. These findings suggest that the associations between puberty timing and subsequent health may be modifiable by dietary intake and adiposity.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial evidence has demonstrated that an earlier timing of puberty is associated with poorer mental and physical health in later life [3][4][5][6][7]. While the underlying mechanisms remain unclear, greater childhood growth and obesity have been associated with both earlier puberty [8] and adverse health outcomes [9][10][11][12][13]. These findings suggest that the associations between puberty timing and subsequent health may be modifiable by dietary intake and adiposity.…”
Section: Introductionmentioning
confidence: 99%